Ruang Dan Memori Dalam Koreografi: Kajian Terhadap Karya Tari Sitespecific Oleh Koreografer Terpilih Di Malaysia - Abdul Wahid, Nurulakmal (2021)
The phenomenon of site-specific performance in Malaysia develops through organized art programs and festivals. Different interpretations of site-specific performance terms are understood to be viewed through the work performed. However, in the global context, site-specific is more focused on a specific location for a performance. The difference in understanding this term has contributed to the choreography concept in site-specific performance. The lack of understanding in structuring a site-specific performance has impacted the quality of works and choreography. This research carries out the objective of understanding the sitespecific term and classifying the relationship between space and memory within the context of site-specific choreography. The purpose is to analyze the use of space and memory in the site-specific choreographic process. This study also focuses on the relationship between space and memory as the key element to form a choreography by exploring a location. The exploration in the choreographic process involves twelve dance works produced in 2009 until 2018 by six local choreographers. The qualitative approach applies by engaging the process of data collection through interview protocols and fieldwork. Analysis of the findings is conducted through the Stage of Performance Work approach by Hunter (2005) and the Memory Input-Output by Herman Ebbinghaus (1962) and appointed by Baddeley (1997). The findings contribute to a specific restructuring of site-specific choreography in Malaysia involving the composition of the choreographic model as a guide in the process of presentation, teaching, and learning in university and Malaysia arts school